2005
DOI: 10.1182/blood-2004-12-4607
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance induction by bone marrow transplantation in a multiple sclerosis model

Abstract: Experimental autoimmune encephalomyelitis (EAE) in rats is a highly valuable model of multiple sclerosis (MS) because it mimics major hallmarks of the human disease. EAE induced with myelin-oligodendrocyte-glycoprotein (MOG) in DA rats is relapsing/ remitting, and lesions in the central nervous system show inflammation, demyelination, and axonal and neuronal loss. Recently, bone marrow transplantation (BMT) was introduced as a novel strategy to treat MS, but its efficiency and the underlying mechanism are deba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 46 publications
(70 reference statements)
0
32
0
1
Order By: Relevance
“…46 Recently, one of these latter studies was published using CY/rATG and it reported no deaths among 21 patients with relapsing-remitting MS. 31 There is a controversy regarding the analysis of the immune system modifications as increases in naive CD4 þ T cells over memory cells 20 and the fact that more intensive regimens seem to present better results than less intensive regimens. 19,26,47 On the other hand, some studies have shown that non-myeloablative conditioning regimens containing CY þ /Àanti-T-cell antibodies induce deep changes in the immune system of patients with autoimmune diseases, with an increase in regulatory subsets of cells and of naive T cells, improvement in TCR diversity and re-establishment of the auto-tolerant state. 48,49 The implications of these findings in clinical studies are still to be seen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Recently, one of these latter studies was published using CY/rATG and it reported no deaths among 21 patients with relapsing-remitting MS. 31 There is a controversy regarding the analysis of the immune system modifications as increases in naive CD4 þ T cells over memory cells 20 and the fact that more intensive regimens seem to present better results than less intensive regimens. 19,26,47 On the other hand, some studies have shown that non-myeloablative conditioning regimens containing CY þ /Àanti-T-cell antibodies induce deep changes in the immune system of patients with autoimmune diseases, with an increase in regulatory subsets of cells and of naive T cells, improvement in TCR diversity and re-establishment of the auto-tolerant state. 48,49 The implications of these findings in clinical studies are still to be seen.…”
Section: Introductionmentioning
confidence: 99%
“…13,[18][19][20] Since the first HSCT reported by Fassas et al, 21 in 1997, more than 300 HSCTs have been performed in MS patients worldwide. [22][23][24] The EBMT (European Group for Blood and Marrow Transplantation) has published the largest samples.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted others and us to hypothesize that restoration of self tolerance could be mediated by the normalization of immune regulatory mechanisms. In an animal model of multiple sclerosis, there was an increase of CD4+CD25+ T cells after syngeneic bone marrow transplantation and this was seen in connection with attenuation of active disease and protection from induction of relapses (5). In humans, enumeration of CD4+CD25[high] T cells in juvenile idiopathic arthritis patients after AHSCT showed recovery of the pre-treatment frequency of Tregs at 6 months post-transplant, and a continued increase for the remaining 12-month follow-up period (6).…”
Section: Sergio Romagnanimentioning
confidence: 99%
“…4 In this respect there has been increasing recognition that total myeloablation may not necessarily provide the best balance between benefi ts and risks, and that autologous HSCT could be used to support safer, better tolerated forms of intensive immuno-ablation. 5 In addition, there has been considerable discussion about the role of TBI based regimens in certain diseases where radiation may exacerbate specifi c conditions and generic late effects. 6 Ultimately, the results of phase III trials should be available in scleroderma, multiple sclerosis and Crohn's disease to prove initial proof of principle of the future role of autologous HSCT in these diseases.…”
Section: Choice Of Conditioning Regimen Dr John a Snowden Director Omentioning
confidence: 99%
See 1 more Smart Citation